2004
DOI: 10.2174/0929867043364315
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors for Proteins Endowed with Catalytic and Non-Catalytic Activity which Recognize pTyr

Abstract: Reversible phosphorylation of Tyr residues in proteins plays a central role in the transduction of signals. For both SH2 domains and for protein tyrosine phosphatases (PTPs) the phosphate group of phosphotyrosine (pTyr) of peptides provides a key affinity element, but its highly charged nature and its hydrolytic lability render it unsuitable in inhibitor design. The research in the recent years has been addressed to find pTyr bioisosters devoid of the phenylphosphate moiety and more potent inhibitors with less… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 132 publications
0
8
0
Order By: Relevance
“…on C-␣ atoms is only 0.45 Å). Second, a superposition of PTP1B in complex with four inhibitors crystallized in three crystal systems revealed that all ligands induce very similar conformations of the protein, except for differences in two surface loops (Glu 115 -Lys 120 and Lys 128 -Glu 132 ) and at the N terminus (residues [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18], where the His 6 affinity tag is attached and ␤-octyl glucoside binds. Finally, a superposition of the apo-and complexed structures reveals that inhibitors induce two major conformational changes, after excluding the flexible regions identified in the apostructures.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…on C-␣ atoms is only 0.45 Å). Second, a superposition of PTP1B in complex with four inhibitors crystallized in three crystal systems revealed that all ligands induce very similar conformations of the protein, except for differences in two surface loops (Glu 115 -Lys 120 and Lys 128 -Glu 132 ) and at the N terminus (residues [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18], where the His 6 affinity tag is attached and ␤-octyl glucoside binds. Finally, a superposition of the apo-and complexed structures reveals that inhibitors induce two major conformational changes, after excluding the flexible regions identified in the apostructures.…”
Section: Resultsmentioning
confidence: 99%
“…Similar results were also observed when an antisense oligonucleotide was injected into mice (5). These compelling biological results coupled with the wealth of structural data, which have been generated since the crystal structure of PTP1B was determined in 1994 (6), have contributed to the rapid design of many potent inhibitors (7)(8)(9)(10)(11)(12)(13). Unfortunately, poor physicochemical properties have limited their development as drug candidates.…”
Section: Protein-tyrosine Phosphatase 1b (Ptp1b)mentioning
confidence: 99%
“…A number of PTP1B inhibitors containing highly charged non-hydrolyzable phosphonate mimetics have been reported (7)(8)(9)(10)(11)(12)(13). Poor membrane permeability, however, has limited their development as drug candidates.…”
mentioning
confidence: 99%
“…Similar problems are also encountered in the development of inhibitors directed against pTyr-binding domains. However, unlike the latter family of compounds, for which a large number of pTyr mimetics have been examined, 44,45 significantly fewer pThr/pSer mimetics have been reported. 4650 Our current paper reports the synthesis and PBD-binding affinities of peptides containing a variety of pThr/pSer mimetics, many of which have not yet been examined within the context of PBD-binding peptides.…”
Section: Introductionmentioning
confidence: 99%